Health and Characteristics of Australian Apple Growing Soils - Marcus Hardie; Garth Oliver; William Cotching; Brianna Walker; Rachel Lancaster; Nigel Swarts (Applied and Environmental Soil Science)
Despite being the highest value fruit crop in Australia, little is known about the types and condition or “health” of Australia’s apple growing soils. This study is unique in being the first to report the condition and characteristics of Australia’s apple growing soils; it provides essential baseline data for future monitoring of soil health in apple production systems, as well as soil physical and chemical data required for the development of perennial soil-tree-climate models. Soil chemical and physical properties were measured at 34 orchards, across five states. Soils were assessed for water retention, hydraulic conductivity, bulk density, macroporosity, organic carbon, CEC, ESP, pH, and EC. Despite high to very high levels of organic carbon, most topsoils were moderately to poorly structured. Around one-third to half of all sites showed evidence of poor aeration or impeded drainage, whilst 10 of the 34 sites were prone to nutrient leaching. Plant available soil water (PAWC) varied greatly between sites from 31 mm to 170 mm from 0 to 60 cm depth and between sites within the same soil order. Whilst topsoils had high to very high levels of organic carbon (average: 2.46%), they were otherwise poorly structured, with higher than expected bulk density (average: 1.32 g/cm3) and lower than expected air capacity (average: 9.97%) and macroporosity (average: 1.75%). Subsoils were also found to have little soil water availability (average: 15.39 mm/100 mm), low air capacity (average: 5.28%), and low CEC (average: 8.12 cmol (+) kg−1). Notably, 10 of the 34 sites had less than 6 cmol (+) kg−1 CEC throughout the entire soil profile, indicating potential risk of nutrient leaching. This study indicates that apple growing soils require careful management to improve topsoil structure, and to maintain or increase soil carbon, as well as use of soil moisture sensors to schedule irrigation. In addition, some sites also require improved subsoil drainage and care to ensure fertigation and irrigation do not result in leaching of nutrients beneath the root zone.